Autophagy and immunity – insights from human herpesviruses - Williams, Luke; Taylor, Graham (Frontiers in Immunology, 2012)
The herpesviruses are a family of double-stranded DNA viruses that infect a large variety of organisms. Having co-evolved with their hosts over millennia, herpesviruses have developed a large repertoire of mechanisms to manipulate normal cellular processes. Given the important role of autophagy in cells, this pathway is a target for manipulation by herpesviruses. Here we describe the ways that human herpesviruses interact and interfere with the cellular autophagy machinery in order to escape innate and adaptive immunity. Recent research on the human herpesvirus Epstein-Barr Virus (EBV) suggesting that localisation within the nucleus can shelter viral proteins from autophagy is also discussed.